Home in the Poetry of Saudi Distinguished Poets: Abdullah Al-Faisal a Case in Point (3): Home in the Poetry of Saudi Distinguished Poets - Dahami, Yahya (Nady Al-Adab : Jurnal Bahasa Arab, 2024)
The diversity of poetry, the gifts of literature, the elegance of language, and the inventiveness of poets are manifestations of the homeland. It is common knowledge that a large amount of poetry has been sacrificed for the homeland and that a great number of Saudi poets have written and are composing golden letters in honor of their homeland, the Kingdom of Saudi Arabia. It is the homeland, the everlasting love, and it constantly will be the homeland, regardless of how forcefully the poet demands it. The final section of this three-part paper seeks to demonstrate Abdullah Al-Faisal's competence, knowledge, and proficiency through one of his poems while also highlighting his allegiance to the vast country to which he belongs. After briefly discussing poetry and its value, the study examines the Kingdom of Saudi Arabia: Poetry and the concept of Homeland before reviewing the words of the poet Abdullah Al-Faisal's career. This study is primarily focused on the poem "The Redemption" through its critical-analytical-descriptive approach. Following that, a conclusion wraps up the investigation. An analysis of a few lines from the poem "The Redemption" revealed the breadth and depth of the concept of the homeland. The study employed Al-Faisal's poetry to express his affection for his homeland. It demonstrates his unwavering commitment to his close bond with his land.